Encapsulation of Green Tea Extract in Nanoliposomes and Evaluation of its Antibacterial, Antioxidant and Prebiotic Properties - B Noudoost; N Noori; Gh Amo Abedini; H Gandomi; A Akhondzadeh Basti; A Jebeli Javan; F Ghadami (Institue of Medicinal Plants, ACECR, 2015)
Background: The application of natural compounds including green tea extract (GTE) in food and pharmaceutical industries is limited. Encapsulation in nanoliposomes could be used as a delivery system to protect these compounds during processing and storage. Objective: In this study encapsulation of green tea extract in nanoliposomes and evaluation of its antibacterial, antioxidant and prebiotic properties were evaluated. Methods: GTE was encapsulated in liposomes by thin film layer method and reached to nanoscale with sonication. The prebiotic activity of 1% nanoliposomal GTE was evaluated on the growth of lactobacillus casei and bifidobacterium lactis in MRS broth medium. Furthermore, the antioxidant activity of nanoliposomal GTE was estimated by DPPH assay. The antibacterial activity of nanoliposomal GTE against Bacillus cereus (ATCC11778), Salmonella typhimurium 138 phage type 2, E. coli O157:H7 and Listeria monocytogenes (ATCC19118) was determined using well diffusion technique. Results: The mean diameter of nanoliposomes was about 44.7± 1.9 nm and had 0.203 ±0.014 polydispersity index. Entrapment eﬃciency of nanoliposomal GTE under the optimum conditions was 97%. Antibacterial activity of GTE was signiﬁcantly increased after encapsulation in nanoliposomes. The strongest antibacterial activity of nanoliposomal GTE was seen against listeria monocytogenes with an inhibition zone of 16.2 mm while E. coli was the most resistance strain with an inhibition zone of 14 mm. Furthermore, the antioxidant activity of GTE was signiﬁcantly increased after nanoliposome encapsulation since the IC50 value of nanoliposomal GTE was decreased to 1.78 &mug ml-1. Moreover, addition of 1 % nanoliposomal GTE enhanced the growth rate of Lactobacillus casei and Bifidobacterium lactis to a signiﬁcant extent. Conclusion: Nanoencapsulation effectively enhanced beneficial properties of GTE.